2010 IEEE Frontiers in Education Conference (FIE) 2010
DOI: 10.1109/fie.2010.5673337
|View full text |Cite
|
Sign up to set email alerts
|

Animations as a tool for enhancing teaching and learning outcomes in Civil Engineering courses

Abstract: On behalf of our two host schools and three sponsoring societies, welcome to the 40th Annual Frontiers in Education Conference. Deans of Engineering James Aylor of the University of Virginia and Richard Benson of Virginia Tech welcome you to Arlington and invite you to visit their schools in Charlottesville and Blacksburg. Three professional societies -ASEE Educational Research and Methods Division (ERM), IEEE Education Society, IEEE Computer Society -have collaborated for many years to establish the tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The study has revealed that "animations can serve as effective multimedia tools to engage students while facilitating and enhancing the student learning experience by explaining difficult concepts through visual means instead of the traditional way of heavy textual based presentation" [22]. This conclusion comes from the fact that 67% of respondents indicated that animations and simulations in courses enabled them to grasp difficult concepts more easily.…”
Section: Discussion and Lesson Learntmentioning
confidence: 94%
“…The study has revealed that "animations can serve as effective multimedia tools to engage students while facilitating and enhancing the student learning experience by explaining difficult concepts through visual means instead of the traditional way of heavy textual based presentation" [22]. This conclusion comes from the fact that 67% of respondents indicated that animations and simulations in courses enabled them to grasp difficult concepts more easily.…”
Section: Discussion and Lesson Learntmentioning
confidence: 94%
“…To help increase the attention span in the STEM classroom, Felder and co-workers have been some of the biggest enthusiasts of the implementation of active learning strategies and methods in large classes and in how to incorporate them without sacrificing content coverage (Felder, 1997;. Some of these approaches may be implemented in what could be seen as interactive lecturetype classes, encompassing strategies and methods such as quizzes (Aravinthan & Aravinthan, 2010;Bell, 1997;Cohen & Sasson, 2016;Cox & Clark, 1998), Minute Paper (Domokos & Huey, 2021;Levin-Banchik, 2022;Weaver & Cotrell, 1985), and Think-Pair-Share (Gok, 2018;Kaddoura, 2013;Lyman, 1981). Additionally, this study considers the following strategies and methods, which are described in detail in Table 5 of Appendix 1: Team-Based Learning (Leupen, 2020;Michaelsen & Sweet, 2008), Flipped Classroom (al Mamun et al, 2022Lage et al, 2000), Peer Instruction (Mazur, 2013;Tullis & Goldstone, 2020), Gamification/Game-Based Learning (Kapp, 2012;Patil & Kumbhar, 2021), Case…”
Section: Active Learning Approachesmentioning
confidence: 99%
“…This is supported by research on interpolated testing in which a lecture is punctuated by testing events—a protocol demonstrated to improve student performance (Szpunar et al, 2014). Research offering online quizzes to students as a learning tool demonstrated that when students were left to their own devices, frequency of quiz attempts tended to occur in massed fashion prior to an examination (Aravinthan & Aravinthan, 2010), suggesting that spacing protocols in classroom environments may require some level of instructor enforcement (e.g., Trumbo et al, 2016). It is not clear if students with relatively low WMC self-monitored and adjusted the spacing of their quiz attempts in order to account for their cognitive abilities.…”
Section: Limitations/moderators Relating To Student Characteristicsmentioning
confidence: 99%